Improved dairy cows in Uganda: Pathways to poverty alleviation and improved child nutrition - Kabunga, Nassul S. (International Food Policy Research Institute, 2014)
The introduction and dissemination of improved dairy cow breeds in Uganda is arguably the most significant step taken to develop a modern and commercial dairy industry in the country over the last two decades. This study uses a nationally representative sample of Ugandan households to rigorously examine the impact of adoption of improved dairy cow breeds on enterprise-, household-, and individual child-level nutrition outcomes. We find that adopting improved dairy cows significantly increases milk productivity, milk commercialization, and food expenditure.